"Anywhere but here": Querying spatial stigma as a social determinant of health among youth of color accessing LGBTQ services in Chicago's Boystown. (September 2018) - Felner, Jennifer K.; Dudley, Terry D.; Ramirez-Valles, Jesus
Abstract: The link between stigma and negative health outcomes is established, yet available research infrequently considers the complex intersection of place, race, and class-based stigma and how this stigma shapes opportunities and health among marginalized groups. Furthermore, scholarship on the relationship between stigma and health often fails to include the voices of the stigmatized themselves. This exclusion renders their lived-experiences hidden and their insight devalued, producing findings with limited validity to promote health equity and social change. In this article, we explore intersecting place, race, and class-based stigmas, or spatial stigma, as a social determinant of health among youth of color (YoC) accessing LGBTQ-specific services in the Chicago's White, middle-class gay enclave, Boystown. Qualitative data were collected within the context of a youth participatory action research study with 11 youth researchers (ages 18–24). Data sources included critical autoethnography, focus groups with current and former LGBTQ service patrons, and individual interviews with LGBTQ service providers. Emergent thematic patterns illuminate how the stigmatization of YoC based on place, race, and class (i.e., being from poor and low-income, racialized South and West sides communities) impacts their opportunities in the neighborhood and access to health-supporting resources. These findings may be useful for practitioners and policy makers who aim to promote health equity among marginalized young people and add to the growing body of literature on health effects of spatial stigma among marginalized communities. Highlights: Participatory action research with youth accessing LGBTQ resources in Boystown. Youth of color from Chicago's South and West sides are outsiders in Boystown. Youth of color experience spatial stigma at the nexus of place, race, and class. This stigma manifests through policing, tokenization, and peer (re)stigmatization. Spatial stigma shapes youth of color's opportunities and access to resources.